2007
DOI: 10.1007/s11136-007-9283-4
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life (HRQoL) domains most valued by urban isiXhosa-speaking people

Abstract: Despite being asked specifically to answer the questions in relation to their health status, the participants apparently did not differentiate between general quality of life (QoL) and specific HRQoL. It appears that members of an under-resourced community regard socioeconomic and service delivery aspects of their lives as integral to their perceived state of health. It may be that it is not possible to separate factors relating to general quality of life from those specifically related to HRQoL in an under-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…The associations of PMUD with neighborhood traffic safety and neighborhood crime safety found in our study is in agreement with other studies that show that living in a safe environment appears to be a basic requirement for a good HRQoL. 46 Finally, we found that individuals living in neighborhoods that are safe from crime have more chance to have unimpaired MUD, PUD, and PMUD than individuals living in unsafe neighborhoods. This fact it is not surprising because the findings from our study come from a middle income country with different sociopolitical and cultural characteristics, and both safety and security have been major social concerns in many metropolitan areas.…”
Section: Discussionsupporting
confidence: 92%
“…The associations of PMUD with neighborhood traffic safety and neighborhood crime safety found in our study is in agreement with other studies that show that living in a safe environment appears to be a basic requirement for a good HRQoL. 46 Finally, we found that individuals living in neighborhoods that are safe from crime have more chance to have unimpaired MUD, PUD, and PMUD than individuals living in unsafe neighborhoods. This fact it is not surprising because the findings from our study come from a middle income country with different sociopolitical and cultural characteristics, and both safety and security have been major social concerns in many metropolitan areas.…”
Section: Discussionsupporting
confidence: 92%
“…As a result of the difference in socioeconomic statuses, differences could be present in the quality of life domains in stroke patients from this low-income country. It has been reported in a South African study that people living in low socioeconomic communities, considered the environmental domain as the most important domain for quality of life (Jelsma, Mkoka & Amosun 2008). Aspects that affected quality of life included access to medical services, owning a brick home (with water, electricity and sanitation) and having sufficient food.…”
Section: Introductionmentioning
confidence: 99%